Deaf history unveiled : interpretations from the new scholarship - Van Cleve, John V. (Gallaudet University Press, 1993)
Since the early 1970s, when Deaf history as a formal discipline did not exist, the study of Deaf people, their culture and language, and how hearing societies treated them has exploded. Deaf History Unveiled: Interpretations from the New Scholarship presents the latest findings from the new scholars mining this previously neglected, rich field of inquiry. The sixteen essays featured in Deaf History Unveiled include the work of Harlan Lane, Renate Fischer, Margret A. Winzer, William McCagg, and twelve other noted historians who presented their research at the First International Conference on Deaf History in 1991. Deaf History Unveiled travels from a monastery, in 16th-century Spain to banquets planned by and for Deaf people in 19th-century France, from the presses of a once-activist school newspaper in pre-Depression New Jersey to the founders & deaf education in Russia to the present. Readers will discover the new themes driving Deaf history, including a telling comparison of the similarities in experience among Deaf people and African Americans, both minorities with identifying characteristics that cannot be hidden to thwart bias. The paternalism of hearing societies resounds in separate studies of deaf education and the opportunities afforded deaf people in the United States, Italy, and Hungary. Adding to its intrigue, the new research in this outstanding volume provides evidence for the previously uncredited self-determination of Deaf people in establishing education, employment, and social structures common through-out the Northern hemisphere. Historians, teachers, and students alike will prize Deaf History Unveiled as a singular collection of insights that will change historical perspectives on the Deaf experience worldwide.